2002
DOI: 10.1002/lsm.10006
|View full text |Cite
|
Sign up to set email alerts
|

Laser soft palate “stiffening”: An alternative to uvulopalatopharyngoplasty*

Abstract: Laser stiffening of soft palate is simple, safe and effective for reduction of length and fluttering of the soft palate in the canine model. Clinical studies are warranted to evaluate its efficacy as an office treatment for snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…3,4 Er:YAG laser irradiation, in contrast, is reported to be a noninvasive and more effective method available for treating snoring. 12,16 The method uses Er:YAG laser energy that causes contraction of the collagen fibers and provides opening of the airway, which decreases snoring with a 90% success rate.…”
Section: Effects Of Er:yag Laser In the Rat Soft Palatementioning
confidence: 90%
See 3 more Smart Citations
“…3,4 Er:YAG laser irradiation, in contrast, is reported to be a noninvasive and more effective method available for treating snoring. 12,16 The method uses Er:YAG laser energy that causes contraction of the collagen fibers and provides opening of the airway, which decreases snoring with a 90% success rate.…”
Section: Effects Of Er:yag Laser In the Rat Soft Palatementioning
confidence: 90%
“…Wang et al 3 used Nd:YAG laser as an alternative to uvulopalatopharyngoplasty on an animal model and demonstrated the stiffening and elevation of the soft palate. They reported that Nd:YAG laser seemed to be effective in palate shortening and stiffness of the canine, but it had to be determined if it would produce the same effects in human subjects.…”
Section: Effects Of Er:yag Laser In the Rat Soft Palatementioning
confidence: 98%
See 2 more Smart Citations
“…11 It is also believed that development of soft palate fibrosis following laser palatoplasty results in increased soft palate stiffness, which may lead to a decreased likelihood of soft palate displacement during exercise. 11 It is also believed that development of soft palate fibrosis following laser palatoplasty results in increased soft palate stiffness, which may lead to a decreased likelihood of soft palate displacement during exercise.…”
mentioning
confidence: 99%